Dr. Bhau Daji Lad Museum - Ghosh, Ayan (2023)
The idea for setting up a museum was mooted in 1850 when preparations were underway for the ‘Great Exhibition of the Works of Industry of all Nations’ to be held at the Crystal Palace in London (1851). The museum was established at Town Hall. With the transfer of power to Queen Victoria (1858), a meeting was called at Town Hall to raise funds for building a new museum.